Design of hydroxylated MnO2 nano-bricks for high-performance supercapacitors. (2022) - Kumari, Sumi; Bhatia, Deepak
Abstract: High surface area 3D architecture of H–MnO2 nano bricks (NBs) on Cu substrate is developed by employing controlled electrodeposition of Mn on Cu substrate followed by high-temperature thermal treatment in hydrogen atmosphere. The electrochemical activity of the H–MnO2 NBs as a supercapacitor electrode material shows high specific and areal capacitance of 1410 F/g and 295 mF/cm 2, respectively along with high cycling stability (only 5% loss of initial specific capacitance after 3000 cycles at a current density of 2.5 A/g). This electrode exhibits an excellent energy density of 22.51 Wh/kg and a power density of 20.44 kW/kg, even at a high current density of 100 A/g. The excellent electrochemical performance of the H–MnO2 NBs as supercapacitor electrode is due to the active material's enhanced electron and ion conductivity, which is due to the presence of hydroxyl groups on the MnO2 NBs surface.